PENGGUNAAN MEDIA PEMBELAJARAN MICROSOFT OFFICE POWERPOINT PADA POKOK BAHASAN PELUANG - Rahma Faelasofi, author (JURNAL E-DUMATH, 2015)
The objectives of this research was to solve how to increase the studentsâ average result especially on the subject of Opportunities. This study aims to determine whether the studentsâ average result of the student Mathematic Education Department STKIP Muhammadiyah Pringsewu Lampung (STKIP MPL) in the academic year of 2013-2014 using instructional teaching media using Microsoft Office PowerPoint on the subject of Opportunities, is better than the studentsâ average result without using instructional teaching media using Microsoft Office PowerPoint. This research is a quantitative approach, with a quasi-experimental research methods. The population was all of the students in third grade of the Mathematic Education Department STKIP MPL in the academic year of 2013-2014. The samples of the research were taken by using the cluster random sampling technique. Based on hypothesis test, it can be included that: 1) there are differences in studentsâ average results between experiment class that used computer teaching media using Microsoft Office PowerPoint and the kontrol class without using a computer teaching media using Microsoft Office PowerPoint; 2) the studentsâ average results at experiment class that used a computer teaching media using Microsoft Office PowerPoint higher than the studentsâ average results in kontrol class.Keywords: Teaching Media, Microsoft Office PowerPoint, Subject of Opportunities